Effects of light-emitting diode spectral combinations on growth and quality of pea sprouts under long photoperiod - Zhang, Siqi; Guo, Xiaolei; Li, Junyan; Zhang, Yinghua; Yang, Youming; Zheng, Wengang; Xue, Xuzhang (Frontiers in Plant Science, 2022)
Pea sprouts have rich nutrition and are considered good for heart health. In this study, the kaspa peas and black-eyed peas were chosen to clarify the effect of different LED spectral combinations on the growth, yield, and nutritional quality of pea sprouts under long photoperiod (22 h light/2 h dark). The results showed that the two pea varieties responded differently to light spectral combinations. Black-eyed pea sprouts had higher plant height, fresh weight per plant, dry weight per plant, soluble sugar content, and lower malondialdehyde (MDA) content than kaspa peas under the same light treatment. Compared with white light, red-to-blue ratio of 2:1 significantly increased peroxidase (POD) and superoxide dismutase (SOD) activity, soluble sugar and soluble protein content of kaspa pea sprouts, and decreased MDA content of black-eyed pea sprouts. Blue light was negatively correlated with the plant height of pea sprouts and positively correlated with SOD activity, vitamin C, soluble sugar, and soluble protein content. Antioxidant capacity, yield, and nutritional quality of black-eyed pea sprouts were higher than those of kaspa pea sprouts under the same light treatment. Blue light improved the nutritional quality of pea sprouts. Compared with other light treatments, the red-to-blue ratio of 2:1 was more conducive to improving the antioxidant capacity and nutritional quality of pea sprouts under long photoperiod.